Effects of different energy and protein levels on growth performance, carcass traits, and meat quality of Pekin ducks - Zhao, P. Y.; Ao, X.; Zhao, W.; Zhou, L. (Frontiers in Veterinary Science, 2025)
This study was conducted to determine the effects of different energy and protein levels on growth performance, carcass traits, meat quality, and taste scores of Pekin ducks. A total of 1,800 numbers of 15-day-old ducks (10 replicate pens, 60 birds/pen, 819 ± 18 g/duck) were blocked based on body weight (BW) and randomly allotted to three treatments with different metabolizable energy (ME) and crude protein (CP) levels in this 28-day experiment. Dietary treatments were as follows: (1) low energy protein (LEP), 3,150 kcal/kg and 16% for the grower diet and 3,250 kcal/kg and 15% for the finisher diet; (2) medium energy protein (MEP), 3,250 kcal/kg and 16.5% for the grower diet and 3,350 kcal/kg and 15.5% for the finisher diet; (3) high energy protein (HEP), 3,350 kcal/kg and 17% for the grower diet and 3,450 kcal/kg and 16% for the finisher diet. During days 15–28, body weight gain (BWG) in the LEP group was higher (p < 0.05), whereas FI, F/G, and caloric conversion were lower (p < 0.05) in the MEP and HEP groups. During days 29–42, birds fed with LEP and HEP diets had lower (p < 0.05) BWG but higher F/G and caloric conversion compared with those fed with the MEP diet. Birds fed with the LEP diet had higher (p < 0.05) BWG than those fed with MEP and HEP diets throughout the experiment. The abdominal fat yield in the LEP group was lower (p < 0.05) than in the HEP group. Birds fed with the LEP diet had higher (p < 0.05) left breast meat yields than those fed with MEP and HEP diets. The roasting loss in the LEP and HEP groups was lower (p < 0.05) than in the MEP group. Birds fed with LEP and HEP diets had higher (p < 0.05) comprehensive scores, flavor scores, scent scores, and taste scores, but lower color scores compared with those fed with the MEP diet. In summary, the LEP diet with the lowest cost may be the most appropriate based on growth performance, roasting loss, and taste scores.